2017
DOI: 10.1021/jacs.6b13051
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Catalyzed Copolymerization of Ethylene and Alkyl Acrylates

Abstract: Ni(II) complexes bearing an o-bis(aryl)phosphinophenolate ligand were synthesized as catalysts for copolymerization of ethylene and alkyl acrylates. When the P-bound aryl group was 2,6-dimethoxyphenyl group, one of the oxygen atoms in the methoxy groups coordinated to the nickel center on its apical position. This complex was a highly active catalyst without any activators to give highly linear and high molecular weight copolymers. The structures of the copolymers were determined by H andC NMR to clarify that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
168
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(173 citation statements)
references
References 42 publications
2
168
1
2
Order By: Relevance
“…[83] These nickel complexes can mediate efficient ethylene copolymerization with fundamental polar monomers,including various acrylates.Surprisingly,very high catalytic activities (up to 3230 kg mol À1 h À1 ), extremely high copolymer molecular weights (M n up to 143,000), and moderate comonomer incorporation (0.3-4.5 mol %) were achieved. [83] These nickel complexes can mediate efficient ethylene copolymerization with fundamental polar monomers,including various acrylates.Surprisingly,very high catalytic activities (up to 3230 kg mol À1 h À1 ), extremely high copolymer molecular weights (M n up to 143,000), and moderate comonomer incorporation (0.3-4.5 mol %) were achieved.…”
Section: Methodsmentioning
confidence: 99%
“…[83] These nickel complexes can mediate efficient ethylene copolymerization with fundamental polar monomers,including various acrylates.Surprisingly,very high catalytic activities (up to 3230 kg mol À1 h À1 ), extremely high copolymer molecular weights (M n up to 143,000), and moderate comonomer incorporation (0.3-4.5 mol %) were achieved. [83] These nickel complexes can mediate efficient ethylene copolymerization with fundamental polar monomers,including various acrylates.Surprisingly,very high catalytic activities (up to 3230 kg mol À1 h À1 ), extremely high copolymer molecular weights (M n up to 143,000), and moderate comonomer incorporation (0.3-4.5 mol %) were achieved.…”
Section: Methodsmentioning
confidence: 99%
“…have evaluated the capability of the ethylene polymerization using some bulky phosphino‐phenolate based nickel complexes (Scheme , B ), which exhibited very high activities of up to 10 7 g PE (mol Ni h) − 1 even at 90 °C. More surprisingly, these nickel catalysts are compatible with some polar vinyl monomers . In addition, Gibson et al showed that some modified SHOP catalyst through the introduction of the bulky group adjacent to the oxygen atom (Scheme , A ) could dramatic increased the catalytic activities .…”
Section: Introductionmentioning
confidence: 97%
“…[21][22][23][24][25] These catalysts were usually ligated by α-diimine, [14,[26][27][28][29][30][31][32] iminopyridyl, [33,34] iminopyrrolyl, [35] salicylaldimine, [36][37][38] and many others. [39] Compared to these branched macrostructures, linear crystalline polyethylenes with high melting temperatures were generally produced by phosphine-containing nickel and palladium catalysts (Scheme 1, A-G) that include SHOP ligands (A), [40][41][42] phosphino-phenolate (B), [43,44] phosphine-sulfonates (C), [45][46][47][48][49] phosphine phosphonic amides (D), [50][51][52] bisphosphine monoxide (E), [53] and other P,N-based ligands (F and G). [54,55] Particularly, some of these catalysts possess comparable even better properties than α-diimine palladium catalysts in copolymerization reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24] These catalysts were generally ligated by α-diimine, [14,[25][26][27][28][29][30][31] iminopyridyl, [32][33][34] iminepyridazine, [35] iminopyrrolyl, [36] salicylaldimine, [37,38] and many others. However, linear crystalline PEs with high melting temperatures were usually produced by phosphine-containing Ni and Pd catalysts with variable ligands that include that include SHOP (Shell higher olefin process) type ligands, [39][40][41] phosphine-sulfonates, [42][43][44][45] phosphino-phenolate, [46,47] phosphine phosphonic amides, [48,49] bisphosphine Qitong Wu and Wenbing Wang contribute equally to the article.…”
mentioning
confidence: 99%
“…monoxide, [50] and many others. Recently, a series of phosphine based Pd catalysts [46,[51][52][53] have emerged as alternatives for copolymerizations of ethylene with polar monomers. Some of these phosphine based catalysts possessed comparable even better properties than α-diimine Pd catalysts in copolymerization reactions.…”
mentioning
confidence: 99%